Functioning of PPR Proteins in Organelle RNA Metabolism and Chloroplast Biogenesis - Wang, Xinwei; An, Yaqi; Xu, Pan; Xiao, Jianwei (Frontiers in Plant Science, 2021)
The PPR (pentatricopeptide repeat) proteins constitute one of the largest nuclear-encoded protein families in higher plants, with over 400 members in most sequenced plant species. The molecular functions of these proteins and their physiological roles during plant growth and development have been widely studied. Generally, there is mounting evidence that PPR proteins are involved in the post-transcriptional regulation of chloroplast and/or mitochondrial genes, including RNA maturation, editing, intron splicing, transcripts’ stabilization, and translation initiation. The cooperative action of RNA metabolism has profound effects on the biogenesis and functioning of both chloroplasts and mitochondria, and, consequently, on photosynthesis, respiration, and development of plants and their environmental responses. In this review, we summarize the latest research on PPR proteins, specifically how they might function in the chloroplast, by documenting their mechanism of molecular function, their corresponding RNA targets, and their specific effects upon chloroplast biogenesis and host organisms.